Usulan Konseptual Sistem Distribusi Cross Docking untuk Meminimumkan Biaya Distribusi pada Industri Retail - Talia Kasih Putri; Hotma Antoni Hutahaean (Widya Teknik, 2016)
For retail industry, the distribution system is the main challenge that must be faced by the company. Choosing the right strategy will save unnecessary costs and reduce distribution time. The distribution time is needed to get products to the warehouse and to get them ready for shipping at the distribution centre. If the distribution time is felt to be too long, it might add costs. The objective of the study was to design a conceptual cross docking distribution system to minimize distribution costs and reduce distribution time by focusing on the product distribution inside the distribution center until the products are delivered to each outlet. Designing a conceptual cross docking distribution system consists of transportation costs, retain costs, the amoun to truck necessities, truck schedules, and the safety stock planning. Results from our calculation showed that the company’s distribution costs werereduced. That is, the distribution costs were down by 62% compared to the current distribution costs. Based on the result, it is concluded that the conceptual cross docking distribution system designed in the present research successfully answered the existing problems. Kata kunci : Cross Docking, Truck Scheduling, Simulation